Prevalence, risk factors, and protective factors of tobacco use among school-going adolescents at drug-abuse hot-spots in Malaysia - Ismail, Rozmi; Hassan, Siti Aishah; Shukor, Md Shafiin; Shafurdin, Nurul Shafini; Hanafi, Norshafizah; Aljaberi, Musheer A.; Lin, Chung Ying; Griffiths, Mark D. (Elsevier, 2025)
The high prevalence rate of tobacco consumption among teenage school students has become a global issue with profound implications for their developmental trajectory. Research conducted at drug-abuse hot-spots as a proximal factor related to tobacco use has been limited. Therefore, the present study examined the prevalence, risk factors, and protective factors of tobacco use among adolescents at drug-abuse hot-spots in Malaysia. Through stratified random sampling, the nationwide sample comprised 3382 school-going adolescents (71.4% male; mean age = 15.35 years [SD = 2.79]). The prevalence of tobacco use was 19.0% for current use and 28.5% for lifetime use. Stepwise logistic regression analysis showed that being male, being an older adolescent, living in urban areas, living many years in the hot-spot area, parental divorce, and having a high external locus of control were significant risk factors for tobacco use. High internal locus of control and good problem-coping skills were protective factors for tobacco use. Policy implications and suggestions for future research are discussed for the prevention and intervention of tobacco use among school-going adolescents.